Al(OH)3 facilitated synthesis of water-soluble, magnetic, radiolabelled and fluorescent hydroxyapatite nanoparticles1. Issue 45 (7th June 2015) - Cui, X.; Green, M. A.; Blower, P. J.; Zhou, D.; Yan, Y.; Zhang, W.; Djanashvili, K.; Mathe, D.; Veres, D. S.; Szigeti, K.
<x xml:space="preserve">Abstract</x> Radiolabelling, magnetic and fluorescent properties are incorporated in one single Fe3O4@HA nanoparticle with potential application as trimodal probes.